1996
DOI: 10.1161/01.hyp.27.3.760
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Actions of Angiotensin II on Microvascular Growth and Arterial Blood Pressure

Abstract: We performed studies to further elucidate the mechanisms of angiotensin II (Ang II)-induced angiogenesis of the microvasculature. Rats were placed on a high salt diet (4% NaCl), and Ang II was infused at a subpressor rate (5 ng/kg per minute) for 3 days. Blood pressure was measured daily for 2 control and 3 infusion days. Microvessel density in the cremaster muscle was measured at the end of the infusion. Vessel density in rats that received subpressor Ang II infusion increased by 12.6% compared with rats that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
183
3
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(200 citation statements)
references
References 17 publications
12
183
3
2
Order By: Relevance
“…Besides the well-known effects on vascular tonus, several studies implicate a role of local RAS in oxidative stress defence [33,34] and in the regulation of angiogenesis [35][36][37][38]. To evaluate the effect of islet RAS on the formation of a new islet vascular system after transplantation, losartan was, in some cases, added to the drinking water of newly transplanted animals.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well-known effects on vascular tonus, several studies implicate a role of local RAS in oxidative stress defence [33,34] and in the regulation of angiogenesis [35][36][37][38]. To evaluate the effect of islet RAS on the formation of a new islet vascular system after transplantation, losartan was, in some cases, added to the drinking water of newly transplanted animals.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (ANG II) has pro-angiogenic effects in various situations such as sponge implant models of angiogenesis, 34 chick chorioallantoic membrane, 35 rat cremaster muscle, 19 rat carotid artery, 36 and cornea. 37 There is evidence that the AT1 receptor mediates the proliferative effects of ANG II 7,19,38 however, the role of the AT2 receptor in these processes is less well understood with reports of pro-, anti-, and no effects on cell growth and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…37 There is evidence that the AT1 receptor mediates the proliferative effects of ANG II 7,19,38 however, the role of the AT2 receptor in these processes is less well understood with reports of pro-, anti-, and no effects on cell growth and angiogenesis. 9,14 -20,39,40 In the present study, we found gene expression for the AT2 receptor to be up-regulated in ROP and AT2-RB to attenuate retinal angiogenesis, indicating that the AT2 receptor promotes retinal endothelial cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…88 Also, coinfusion of rats with Ang II and PD 123199 results in an enhanced blood pressure response, as compared to rats infused with Ang II alone. 89 Although the AT 2 receptor seems to be involved in growth and differentiation, lack of a functional receptor still allows for development of an organism, as illustrated by the establishment of AT 2 knockout mice strains. Data obtained from these mice links the AT 2 receptor to behaviour and to altered blood pressure regulation.…”
Section: Development Of Ang Ii-receptor Binding Substancesmentioning
confidence: 99%